Hydrolysis of glycoside phytoestrogens of the extract from soy germ: A comprehensive study - Minh Chau, Le; Vien, Do Thi Hoa; Phu Ha, Ho (Vietnam Journal of Science and Technology, 2023)
Phytoestrogens which mimic mammalian estrogens structurally and functionally are phenolic compounds. The aglycone phytoestrogens in soy germ including daidzein, genistein, and glycitein are known to have higher biological activity than other derivative forms. This study aimed to assess the potential of pure β-glucosidase to hydrolyze glucoside phytoestrogens from soy germ to increase aglycones content. The optimal conditions for the hydrolysis of aglycones from soy germ evaporated extract included a β-glucosidase content of 4 units/g of defatted soy germ flour and an incubation time of 5.5 hours. Under these conditions, the hydrolysis of β-glycosides, malonyl glycosides, and acetyl glycosides were more than 90 %, 60 %, and 60 %, respectively. The phytoestrogen aglycones content was 31.36 ± 0.06 µmol/g (14.97 ± 0.03 µmol/g daidzein, 7.58 ± 0.05 µmol/g glycitein, and 8.81 ± 0.02 µmol/g genistein), 5 times higher than that of the defatted soy germ flour.